b - Lucknow, Uttar Pradesh. Information and Public Relations Department; Prasad, Sanjay, patron; Shishir, presentator & visualizer; Tripathi, Anshumaan Ram, prastuti evam parikalpit; Sharma, Kumkum, editorial guidance; Lucknow, Uttar Pradesh. Information and Public Relations Department (Lucknow Bharat Book Centre, 2023)
Uttar Pradesh 2022 (varsh 2022 ke tathyon par adharit)
Keywords: Uttar Pradesh -- Reference annual -- 2022-; Economic development -- Uttar Pradesh -- 2022-; History -- Uttar Pradesh -- 2022-; Flora and Fauna -- Uttar Pradesh -- 2022-; Geographical features -- Uttar Pradesh -- 2022-; Cultural heritage -- Uttar Pradesh -- 2022-